Binder jetting additive manufacturing of copper/diamond composites: An experimental study. (October 2021) - Li, Ming; Huang, Jianchi; Fang, Alex; Mansoor, Bilal; Pei, Zhijian; Ma, Chao
Abstract: This study demonstrates the feasibility of fabricating copper/diamond (Cu/Dia) composite samples using binder jetting additive manufacturing for the first time. Binder jetting fabricates parts in two steps: forming green parts with a binder at a low temperature and consolidating the green parts by sintering. The low processing temperature makes binder jetting an excellent candidate to create complex-shaped Cu/Dia parts without causing diamond graphitization. In this study, mixtures of copper-coated diamond powder and pure copper powder were used to print Cu/Dia samples on a binder jetting printer. The printed samples were then sintered under a medium vacuum environment with flowing forming gas (95% nitrogen and 5% hydrogen). The effects of diamond volume fraction (10 vol% and 50 vol%) and sintering temperature (800 °C and 900 °C) on density and porosity, phase composition, and microstructure of Cu/Dia samples were investigated. As the diamond volume fraction increased from 10 vol% to 50 vol%, the sinterability of the powder mixture decreased. Increasing sintering temperature from 800 °C to 900 °C significantly improved sintered bulk density for samples from each powder mixture. When sintering temperature increased from 800 °C to 900 °C, the microstructure evolved from a granular structure to a network structure. In all sintered samples, the distribution of diamond was uniform and there was no sign of diamond graphitization.